THE RELATIONSHIP BETWEEN DIABETES MELLITUS AND THE SEVERITY OF KNEE OSTEOARTHRITIS BASED ON X-RAY IMAGING AT HAJI ADAM MALIK GENERAL HOSPITAL MEDAN - Muhammad Akbar Batubara; Evo Elidar Harahap; Muhammad Aron Pase (MEDALION JOURNAL: Medical Research, Nursing, Health and Midwife Participation, 2024)
Background: Osteoarthritis (OA) is a degenerative joint disease resulting from the destruction of joint cartilage to the formation of subchondral bone and osteophytes that cause pain in the joints. According to WHO, the prevalence of OA in Southeast Asia in 2004 reached 27.4 million people. One of the metabolic disorders that is thought to be a risk factor for OA progressivity is Diabetes Mellitus (DM). Indonesia has the fourth largest number of DM patients with a prevalence of 8.6% of the total population. Current evaluation of OA is based on clinical and radiographic examinations such as X-ray, MRI, CT etc. The Kellgren-Lawrence (KL) system is a validated method to classify the severity of OA into 5 levels. Objective: To determine the relationship between DM and the severity of genu OA based on X-ray photographs at Haji Adam Malik Hospital Medan. Methods: This study used a cross sectional design. The data obtained will then be processed and analyzed with the Chi-Square test, Fisher Exact test, or Kruskal-Wallis test using a data processing program. Results: It was found that DM patients with right genu OA location amounted to 29 people (39.7%), left amounted to 13 people (17.8%), and both amounted to 31 people (42.5%). DM patients with grade 1 severity amounted to 6 people (8.2%), grade 2 amounted to 18 people (24.7%), grade 3 amounted to 25 people (34.2%), and grade 4 amounted to 24 people (32.9%). The results of the Chi-Square test found that there was a significant relationship between DM and the severity of genu OA (p<0.001). Based on Kruskal-Wallis test, there was no significant relationship between DM comorbidity and genu OA severity (p=0.636) and there was no significant relationship between OA severity and HbA1c (p=0.408). Conclusion: There is a significant relationship between DM and the severity of genu OA based on X-ray photos at Haji Adam Malik Hospital Medan.